Cost effectiveness study of using different monitoring modalities in treating severe traumatic brain injury (CESTBI) - Abdullah, Mazlan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Introduction: Injuries are the major causes of death and disability. In Malaysia, injury remains the third leading cause of admission and death in government hospitals. There are two schools of thought in practicing neurotrauma monitoring for patients with severe traumatic brain injury (TBI); the application of the basel~e neuro-monitoring (BNM) and the use of multiple modalities neurotrauma monitoring (M3) which is very expensive. The answer of which of the two monitoring systems is more effective should be sought. Objective: To determine the cost effectiveness of BNM and M3 monitoring modalities in the management of severe TBI in Hospital USM (HUSM), Kelantan Methodology: Sixty-two patients with severe TBI admitted to Neuro-ICU, HUSM who fulfilled the predetermined criteria were purposely selected and grouped according to the surgeon's on call list. The macro and micro costing were performed on each of patient. Barthel Index was used to measure physical performance as an outcome six months after discharge. The equality of the two study groups i.e M3 and BNM, was analyzed by using independent t- test and chi square test, ANCOV A was used to analyze the different in mean total equipment cost between the group ofM3 and BNM by controlling the covariate like age and severity of brain injury, and Repeated Measure ANOVA was used to look for any significant changes in the mean of Barthel Index between the group of M3 and BNM during admission and six months post discharge. ~ Results: The mean total equipment cost of M3 was significantly higher than mean total equipment cost ofBNM at p = 0.049 (mean difference ofRM23.74) after controlling other' variables. The mean difference in Barthel Index after six months was significant between the two groups (p = 0.031), patients who were treated with M3 had higher score [63.7 (SD 30.03)] compared to those who were treated with BNM [46.83 (SD 30.36)]. However, the cost-effectiveness ratio of using. M3 was significantly lower (p~0.031) with a mean ofRM476.29 needed for a unit improvement in mean Barthel Index compared to RM629.12 if we used BNM Conclusion: Although M3 is more costly, the outcome of patients treated with M3 was better than BNM. Therefore we can conclude that the used of multiple neuro-monitoring was more cost effective than the use of only baseline neuro-monitoring in treating severe traumatic brain injury.